2015
DOI: 10.1134/s0036024415080245
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between nanocluster polyoxometallates and low-molecular-weight organic compounds

Abstract: The equilibrium sorption of methanol and benzene vapors by spherical porous nanocluster polyoxometallates with keplerate structures of different compositions (Mo 132 and Mo 72 Fe 30 ) and polyoxometallate (Mo 138 ) with a toroidal structure and patterns in the kinetics of these processes are studied. Changes in the chemical potentials of the sorbates and polyoxometallates, specific Gibbs energies of the interaction of the polyoxometallates with the indicated substances, and the partial molar entropy of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…In addition, it was shown that simpler molybdenum-containing POMs can be used in chemotherapy [115,116]. On the other hand, the initially predicted possibility of the formation of POM conjugates with bioactive substances, drugs, and metal cations using intra-and extrasphere interactions, the possibility of their transport (including iontophoretic) in the body, adds relevance to the studies of POM in the field of targeted drug delivery and diagnostics [117][118][119][120][121][122][123][124][125][126][127][128][129][130][131]. These prospects may relate, inter alia, to immunomodulatory and antiviral agents.…”
Section: Nanocluster Polyoxometalates (Poms)mentioning
confidence: 99%
“…In addition, it was shown that simpler molybdenum-containing POMs can be used in chemotherapy [115,116]. On the other hand, the initially predicted possibility of the formation of POM conjugates with bioactive substances, drugs, and metal cations using intra-and extrasphere interactions, the possibility of their transport (including iontophoretic) in the body, adds relevance to the studies of POM in the field of targeted drug delivery and diagnostics [117][118][119][120][121][122][123][124][125][126][127][128][129][130][131]. These prospects may relate, inter alia, to immunomodulatory and antiviral agents.…”
Section: Nanocluster Polyoxometalates (Poms)mentioning
confidence: 99%
“…POM show stability in weakly acidic solutions, and can be isolated in crystalline or amorphized state. Due to the presence of an internal cavity and pores in the structure of Keplerates, it is possible to introduce various substances inside them, both ions and molecules [337,338], including bioactive substances, which makes them promising in the context of creating nanocapsules for targeted drug delivery [339]. Fig.…”
mentioning
confidence: 99%